Change over time and agreement between clinical markers of disease resolution in dogs with aspiration‐induced lung injury. (17th October 2022) - Chwala, Monica; Hartmann, Faye; Waller, Kenneth; Dusick, Allison; Viviano, Katrina
Abstract: Background: There is a lack of consensus regarding which markers of disease resolution to prioritise when assessing treatment response in client‐owned dogs with aspiration‐induced lung injury. This study describes the change over time and the agreement between the clinical markers used to determine disease resolution. Methods: Physical examination (PE), owner‐reported clinical signs (CS‐O), thoracic radiographs (TXR) scores and C‐reactive protein (CRP) concentrations were determined at enrolment, after 24, 48 and 72 hours, and after 7, 14 and 28 days. Results: PE scores were significantly improved at 48 hours, while CRP initially increased (24 hours) and then decreased (48 hours). PE, CS‐O and CRP significantly improved earlier (7 days) than TXR (14 days). The median number of days to marker normalisation was 7, 9 and 14 for PE, CRP and CS‐O, respectively. Marker agreement was excellent/very good at enrolment and fair/poor during disease recovery. Limitations: Analysis did not control for differences aetiology of aspiration or the lack of standardisation in treatment approach. Conclusions: PE was the earliest and most consistent marker indicating disease resolution. Serial CRP monitoring (72 hours) may provide an objective marker of early treatment response. Alongside PE normalisation, improvement in CS‐O, CRP and TRX may assist in determining disease resolution and guide treatments, including limiting antibiotic exposure in dogs with aspiration‐induced lung injury.